Clay Improvement with Burned Olive Waste Ash - Utkan Mutman (The Scientific World Journal)
Olive oil is concentrated in the Mediterranean basin countries. Since the olive oil industries are incriminated for a high quantity of pollution, it has become imperative to solve this problem by developing optimized systems for the treatment of olive oil wastes. This study proposes a solution to the problem. Burned olive waste ash is evaluated for using it as clay stabilizer. In a laboratory, bentonite clay is used to improve olive waste ash. Before the laboratory, the olive waste is burned at 550°C in the high temperature oven. The burned olive waste ash was added to bentonite clay with increasing 1% by weight from 1% to 10%. The study consisted of the following tests on samples treated with burned olive waste ash: Atterberg Limits, Standard Proctor Density, and Unconfined Compressive Strength Tests. The test results show promise for this material to be used as stabilizer and to solve many of the problems associated with its accumulation.